2021
DOI: 10.1021/acsomega.0c05684
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of an Azo Dye by Cyclodextrins: A Potential Strategy for Water Purification

Abstract: The chemistry of the host–guest complex formation has received much attention as a highly efficient approach for use to develop economical adsorbents for water purification. In the present study, the synthesis of three β-cyclodextrin (β-CD) inclusion complexes with the oil orange SS (OOSS) azo dye as a guest molecule and their potential applications in water purification are described. The complexes were synthesized by the coprecipitation method and characterized by Fourier transform infrared (FTIR) spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…The hydrophobic dye can be removed from the aqueous solution through inclusion complex formation (Saifi et al, 2021). The potential of β-cyclodextrin (β-CD) was studied to remove highly toxic oil orange SS (OOSS) dye by complexion.…”
Section: Complexionmentioning
confidence: 99%
“…The hydrophobic dye can be removed from the aqueous solution through inclusion complex formation (Saifi et al, 2021). The potential of β-cyclodextrin (β-CD) was studied to remove highly toxic oil orange SS (OOSS) dye by complexion.…”
Section: Complexionmentioning
confidence: 99%
“…Fan et al described the removal of methylene blue dye by β-CD-modified Fe 3 O 4 nanoparticles and its reaction with chitosan. The β-CD-based adsorbent reported by Crini et al revealed high adsorption capacities toward Basic Blue 9 (Saifi et al , 2021). Qin et al also reported a “pocket” structure that shows excellent adsorption for the simultaneous removal of organic dyes (rhodamine B and Congo red) and heavy metal ions Cd(II) via a β-CD cross-linked polymer.…”
Section: Methodsmentioning
confidence: 99%
“…OOSS dye encapsulation with the β-CD hydrophobic cavity was confirmed by thermal analysis and FTIR. The complexation induced stability in the matrix, due to host-guest complex formation [94]. In another study, β-CD and ε-polycaprolactone (PCL) composite fibers were prepared by the electrospinning method through the host-guest complexation mechanism, as shown in Figure 4.…”
Section: Application Of Cyclodextrin-based Adsorbents 41 Removal Of Dyesmentioning
confidence: 99%